The mechanism of humoral immune response to allogeneic organ transplantation - A. S. Berkos; G. V. Nikolaev (Вестник трансплантологии и искусственных органов, 2017)
The problem of antibody-mediated rejection of donor organ remains extremely relevant. The main targets of the antibodies are mainly donor HLA-antigens (Human Leucocyte Antigens), expressed, in particular, by the cells of graft vascular endothelium. This review describes the mechanisms of the development of humoral alloimmunity which are based on B-cell recognition of epitopes of donor HLA-molecules and affinity maturation of B-cell receptors in the germinal centers of peripheral lymphatic system. Monitoring of epitope load and cross-reactivity indicators to evaluate HLA-compatibility of donor and recipient plays an important role in the prevention of allograft humoral rejection.